Pemberlakuan Upaya Administrasi Sebagai Primum Remidium Dalam Penyelesaian Sengketa Tata Usaha Negara - Pulung Hudoprakoso (Pusat Riset dan Inovasi Nasional, 2022)
The settlement of state administrative disputes as a result of the issuance of a state administrative decision letter is the authority of the State Administrative Court as a judicial body appointed by the Law governing the State Administrative Court. Administrative efforts are a non-litigation settlement that must be taken before state administrative disputes are submitted to the State Administrative Court. Administrative efforts are expected to be the best solution before citizens submit their problems to the Court, so as to remove the paradigm that the actions of state administrative bodies or officials are always right and cannot be corrected.